Peran Identifikasi Risiko Dalam Mendukung Efektivitas Manajemen Risiko Organisasi: Perspektif ISO 31000:2018 dan COSO ERM - Fadil Azury Farega Rambe; Raihan Ananda Azma (Jurnal Ilmu Ekonomi dan Bisnis, 2026)
Risk identification is a crucial stage in risk management as it serves as the foundation for risk analysis, evaluation, and control processes. This study aims to analyze the role of risk identification in organizational risk management based on the ISO 31000:2018 and COSO Enterprise Risk Management (ERM) frameworks. The research employs a qualitative approach through a literature review by examining various relevant academic sources. The findings indicate that risk identification plays a strategic role in enhancing organizational awareness of potential risks and supporting more effective decision-making. Various techniques can be applied in the risk identification process, including brainstorming, checklists, interviews, SWOT analysis, Failure Mode and Effects Analysis (FMEA), and historical data analysis. The primary output of this process is a risk register containing information on risk sources, causes, and potential impacts. The study concludes that the integrated implementation of ISO 31000:2018 principles and the COSO ERM framework can strengthen organizational risk management practices through a systematic and comprehensive risk identification process.